ChemInform Abstract: Gallium Tribromide Catalyzed Coupling Reaction of Alkenyl Ethers with Ketene Silyl Acetals. Issue 4 (31st January 2013) - Nishimoto, Yoshihiro; Ueda, Hiroki; Yasuda, Makoto; Baba, Akio
Abstract The title reaction is accomplished for various types of alkenyl ethers and ketene silyl acetals.